Evaluation of Importance of Birds from Non-Tidal Wetlands: A Review - Lubal, Maruti J. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Wetlands are the lands transitional between terrestrial and aquatic eco-systems where the water is usually at or near the surface or the land is covered by shallow water. They are most productive, valuable, and provide a wide range of goods and services. Wetland birds rely on waterways for survival and each bird species has its own requirements for food, shelter and breeding sites. Monitoring of wetland birds is an engaging activity that provides researchers with an insight into the functioning and health of wetlands. Despite the high value of services derived from wetlands, they have been systematically drained and filled to support agriculture, urban expansion, and other developments. Agriculture, climate change, draining, dredging, introduced species, pollution, salinization, and urbanization are the major threats to wetlands. In light of these observations, the aim of this review is to update recent information from the available literature relating with the ecosystem services provided by birds from non-tidal wetlands.